HUBUNGAN PERILAKU PETANI DENGAN PRODUKTIVITAS USAHATANI KEDELAI DI KECAMATAN BERBAK KABUPATEN TANJUNG JABUNG TIMUR - Mashudi, Aan; Lubis, Arsyad; Sardi, Idris (Jurnal Ilmiah Sosio-Ekonomika Bisnis, 2018)
Objectives of this study were (1) to determine the behavior of farmers in implementing soubean cuilvation in the districts Berbak(2) to determine the soybean productivity at the farm level in the districts Berbak (3) to determine the relationship between farmer behavior and productivity of soybean farming in the districts Berbak.This study using simple random sampling method and selection of research areas purposively. The sample consisted of 90 people farmers culivate soybean. Analysis of the behavior of farmers in inmplemening soybean cultivation, while the analysis of behavioral relationships with soybean productivity using chi square test with 2 x 2. Of the results showed that the behavior of farmers in implementing soybean cultivation is divided into 3 components : knowledge, attitudes, practices. The behavior of the three components that 63,33% positive farmers know how to soybean cultivation, and the positive attiude of farmers towards soybean cultivation way that three 61,11% as well as farmers who practice how positively soybean 65,55%. Of the three components is known that the behavior of farmers in rural districts Berbak behavior of farmers is 67,77% behave positively in the cultivation of soybeans. Farmers in rural districts Rantau Makmur Berbak average-average soybean farm productivity 14,2 kw/ha. By chi square, there is a real connection between the behavior of farmer with soybean farm productivity in rural districts Berbak.